Understanding the uncomfortable kōkako: the challenge of applying threshold concepts in Māori studies - Meegan Hall; Peter Adds; Mike Ross; Phillip Borell (University of Johannesburg, 2017)
There are Māori studies programmes in all eight New Zealand universities and thousands of Māori studies students enrol each year. However, little research has been done on the scholarship of teaching and learning (SOTL) within the Māori studies discipline. This article investigates, through the process of an integrative literature review, the potential to apply the theory of threshold concepts (Meyer & Land 2006) - the idea that there is a set of transformational concepts that can unlock understanding in any discipline - to the Māori studies discipline. It highlights issues that arise in applying threshold concepts to a relatively new discipline that centres Indigenous knowledge and practices. The transformative elements of Māori studies and the irreversible change that Western epistemologies have caused to Māori studies' knowledge are discussed. The bounded aspect of Māori studies is canvased, as well as the ability of Māori studies to integrate with other cognate disciplines. The troublesome nature of Māori studies content is explored, along with the discursive elements of its formal and coded curricula. Also, the idea of liminality is examined, as a way to demarcate the academic territory of Māori studies and clarify the curriculum. Ultimately, many questions emerge in this article but also opportunities to advance the SOTL research in both threshold concepts as a theory and Māori studies as a discipline. How to cite this article: HALL, Meegan; ADDS, Peter; ROSS, Mike; BORELL, Phillip. Understanding the uncomfortable kōkako: the challenge of applying threshold concepts in Māori studies. Scholarship of Teaching and Learning in the South, %5BS.l.%5D, v. 1, n. 1, p. 91-107, sep. 2017. Available at: <http://sotl-south-journal.net/?journal=sotls&page=article&op=view&path%5B%5D=15>. Date accessed: 12 Sep. 2017. This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/